2016
DOI: 10.4103/0972-2327.186786
|View full text |Cite
|
Sign up to set email alerts
|

Sural sensory nerve action potential: A study in healthy Indian subjects

Abstract: Background:The sural sensory nerve action potential (SNAP) is an important electrodiagnostic study for suspected peripheral neuropathies. Incorrect technique and unavailability of reference data can lead to erroneous conclusions.Objectives:To establish reference data for sural SNAP in age-stratified healthy subjects at three sites of stimulation.Materials and Methods:A prospective study was conducted in 146 nerves from healthy subjects aged between 18 years and 90 years, stratified into six age groups (a = 18-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
(36 reference statements)
0
2
1
1
Order By: Relevance
“…However, the increment of SNAP amplitude in the adjusted method was greater than that reported in a previous study [ 13 ]. In the previous study that tried to find the reference value for sural SNAP parameters with antidromic NCS method, the ratio of the amplitude in different stimulation distances (14 cm and 12 cm) was 1.10 [ 13 ]. Compared to the previous study, the average difference in stimulating distances in the present study was smaller than that in the previous study.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…However, the increment of SNAP amplitude in the adjusted method was greater than that reported in a previous study [ 13 ]. In the previous study that tried to find the reference value for sural SNAP parameters with antidromic NCS method, the ratio of the amplitude in different stimulation distances (14 cm and 12 cm) was 1.10 [ 13 ]. Compared to the previous study, the average difference in stimulating distances in the present study was smaller than that in the previous study.…”
Section: Discussioncontrasting
confidence: 78%
“…This was predictable because the average distance from the stimulation site to recording site (EI) was shorter in ultrasound-guided method. However, the increment of SNAP amplitude in the adjusted method was greater than that reported in a previous study [13]. In the previous study that tried to find the reference value for sural SNAP parameters with antidromic NCS method, the ratio of the amplitude in different stimulation distances (14 cm and 12 cm) was 1.10 [13].…”
Section: Discussionmentioning
confidence: 65%
“…Bei antidromer Stimulation 10, 12 und 14 cm proximal und einer Ableitung am Außenknöchel wurden mit zunehmen dem Abstand niedrigere Amplituden registriert [25]. In or thodromer Technik nahm die Amplitude des sNAP mit der Distanz von Stimulus-und Ableitort ab [26].…”
Section: Distanz Von Stimulations-und Ableitortunclassified
“…The sural/radial nerve amplitude ratio is more sensitive to degradation than any potential for pure sensory nerve function in diabetes or another axonal polyneuropathy [Papanas N et al, 2010;Barnett C et al, 2012]. Although sensory nerve function can be affected by various factors (i.e., BMI, age, and sex), some studies found that the SRAR was more impervious to these factors [Sreenivasan A et al, 2016;Lai Y et al, 2020]. Therefore, the present study has been performed on diabetic patients to compare two electrophysiological methods, including the SRAR and sensory nerve function potential.…”
Section: Introductionmentioning
confidence: 99%